Scientific integrity : Text and cases in responsible conduct of research - Macrina, Francis L. (ASM Press, 2014)
This widely adopted textbook provides the essential content and skill-building tools for teaching the responsible conduct of scientific research. Scientific Integrity covers the breadth of concerns faced by scientists: protection of animal and human experimental subjects, scientific publication, intellectual property, conflict of interest, collaboration, record keeping, mentoring, and the social and ethical responsibilities of scientists.